Factors related to subjective well-being among community-dwelling older adults living alone: A stratified analysis by sex and marital status from the JAGES. - Nana Abe; Nanami Oe; Etsuko Tadaka; Toshiyuki Ojima (PLoS ONE)
Background Previous cross-sectional studies suggest that negative health outcomes such as mortality, social isolation, loneliness, and depression among older adults living alone vary by sex and marital status, with men often worse off than women and unmarried people worse off than married people. However, limited evidence exists from longitudinal studies regarding whether positive health outcomes such as subjective well-being (SWB) also vary by sex and marital status. The focus by sex and marital status on the positive health outcomes and diverse profiles of older adults living alone is important for public health in the near future. Therefore, the purpose of this study was to identify changes in SWB over time and its associated factors by sex and marital status among older adults living alone in the community using a longitudinal study in a representative population. Methods This was a longitudinal study using data from the Japan Gerontological Evaluation Study. This study is the first to reveal differences in SWB and related factors over 3 years among older adults living alone in the community (n = 8,579) who were stratified by sex and marital status (married men, non-married men, married women, and non-married women). Results Women moved to higher levels of SWB than did men, and married individuals moved to higher levels of SWB than did unmarried individuals. Independent functioning factors and interpersonal factors were significantly associated with SWB for married men and married women, but for unmarried women, the association by interpersonal factors was more pronounced, and for unmarried men, only limited emotional support and health promotion activities were significant among the interpersonal factors. Conclusions This study revealed that among older adults living alone, changes in SWB over time and the independent functioning factors and interpersonal factors associated with this change varied by sex and marital status among older people living alone. These findings are useful for policy-making and guiding intervention activities to promote SWB in a society in which the environment for older adults living alone is changing dramatically.